THE SIGNIFICANCE OF USING INTERNATIONAL EXPERIENCES IN THE DEVELOPMENT OF RURAL TOURISM IN UZBEKISTAN - Ibragimov Lutfullo; Usmonov Sardor (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Tourism is gaining importance in the economic environment of countries in today's modern economy. The developing industry ensures the creation of new industries within it. This is because tourism is a service sector and is subject to its laws. That is, it has a variable character based on the needs and demands of tourists participating in the activity. As a product of such needs, rural tourism has entered the field. Since the tourism potential of our country is sufficient for this sector, it is necessary to take necessary measures for its development. In this regard, the conclusions of international experiences are also considered important, and it is also important to pay attention to their achievements and shortcomings. These aspects are taken into account during the article In coming to these conclusions and presenting practical suggestions, the methodological basis of the research was formed as a result of the study of theoretical and practical data, literary sources and publications. The research is based on the connections between theory and practice, and uses methods such as analysis, comparison, analogy and synthesis